ENHANCEMENT EDUCATIONAL PROCESS IN THE CONDITIONS OF INFORMATIVE-COMMUNICATIVE PEDAGOGICAL ENVIRONMENT. - L. Petukhova (Kherson State University, 2010)
In the article are considered the possibilities and conditions of realization informative-communicative pedagogical environment at high school, the ways of educational process expansion in the context of informative-communicative pedagogical environment are also described.